Analysis of the effects of manipulating the space and number of players in small-sided games on the external load demands of futsal athletes in different age categories - Gomes, Leandro Lume; Gomes, Sérgio Adriano; Travassos, Bruno; Nuno Ribeiro, João; Asín-Izquierdo, Iván; Castro, Henrique de Oliveira; Ferreira, Carlos Ernesto Santos (Biology of Sport, 2025)
The study aim was to analyse the effects of manipulating the space and number of players in small-sided games on the external load demands of futsal athletes of different age categories. Fifty-six male futsal players from U15, U17, U19, and adult age categories participated. The study lasted 7 weeks. The first week was for familiarization and evaluations to characterize the sample. In the six subsequent weeks there were six futsal tasks T1 (GK + 2×2 + GK, 20×20 m), T2 (GK + 2×2 + GK, 40×20 m), T3 (GK + 3×3 + GK, 20×20 m), T4 (GK + 3×3 + GK, 40×20 m), T5 (GK + 4×4 + GK, 20×20 m), and T6 (GK + 4×4 + GK, 40×20 m). The external load variables were measured with an inertial measurement unit (IMU), and kinematic (total and relative distance) and mechanical (total distance at high intensity accelerations and decelerations) data were extracted. T2 (133 m 2 ) showed higher values for total distance covered (1248.0±97.6 m) and distances covered at speeds between 12.1 and 18 km/h (407.8±44.7 m) and greater than 18.1 km/h (115.2±28.9 m) compared to T5 (40 m 2 ) and T6 (80 m 2 ). In addition, we observed greater variability in high-intensity accelerations and high intensity decelerations, suggesting that regardless of field size and number of players, relative area might not play as crucial a role in this dimension.